RISK REDUCTION MANAGEMENT MODEL OF SCUBA DIVING IN THAILAND - Tientawach, Piyasak (Academic Journal of Thailand National Sports University, 2019)
The objective of this research was to create a risk reduction management model of diving activities in Thailand. This research was conducted by Delphi technique. The samples of the research consisted of 17 diving experts. Statistics were percentage, median, mode, and interquartile ranges. The results showed as the following five aspects: 1. Diving instructors had to have the requirements of a diving. 2. Divers had to undergo primary diving training. 3. Diving equipment had to meet the standards of working condition. 4. Diving instructors had to know Geographical environment of the diving site for the best decisions. 5. Dangers in diving included chemicals, dangerous animals, plants and the wrong way of diving. Suggestions for the implementation of the research findings were: 1) To establish a Responsible agency should be established, 2)Training sessions for participants in diving activities should be organized, 3) Legislative guidelines to the entrepreneurs should be setup, 4) The authority should make divers adhere to the strict regulations of diving